A 360-degree Holographic Display System for Radiotherapy Treatment Planning. Issue 3 (3rd May 2016) - Lu, Yukying; Lee, Shara Weeyee; Khaw, Kim; Du, Ruxu
ABSTRACT: Beam's Eye View is a commercial software system that is used by radiologists to plan radiotherapy treatment for cancer patients. It utilizes an algorithm that reconstructs a three-dimensional (3D) image from a serial of composite images of both Computed Tomography (CT) and Magnetic Resonance Imaging (MRI). While it is effective, the display of 3D images on a 2D flat screen often creates confusion and limits its efficiency. In this paper, the use of holographic display is proposed. Two different holographic display systems are discussed, including the 4-side pseudo 3D holographic display system and 360-degree spinning holographic display system. The unambiguous holographic display helps the doctor to plan the radiotherapy treatment in a straightforward manner. With further development, it is expected that the proposed technology will soon find practical applications in the hospital. GRAPHICAL ABSTRACT: